Aberrant neural correlates of multisensory processing of audiovisual social cues related to social anxiety: An electrophysiological study - Gan, Shuzhen; Li, Weijun (Frontiers in Psychiatry, 2023)
Social anxiety disorder (SAD) is characterized by abnormal fear to social cues. Although unisensory processing to social stimuli associated with social anxiety (SA) has been well described, how multisensory processing relates to SA is still open to clarification. Using electroencephalography (EEG) measurement, we investigated the neural correlates of multisensory processing and related temporal dynamics in social anxiety disorder (SAD). Twenty-five SAD participants and twenty-three healthy control (HC) participants were presented with angry and neutral faces, voices and their combinations with congruent emotions and they completed an emotional categorization task. We found that face-voice combinations facilitated auditory processing in multiple stages indicated by the acceleration of auditory N1 latency, attenuation of auditory N1 and P250 amplitudes, and decrease of theta power. In addition, bimodal inputs elicited cross-modal integrative activity which is indicated by the enhancement of visual P1, N170 and P3/LPP amplitudes and superadditive response of P1 and P3/LPP. More importantly, excessively greater integrative activity (at P3/LPP amplitude) was found in SAD participants, and this abnormal integrative activity in both early and late temporal stages was related to the larger interpretation bias of miscategorizing neutral face-voice combinations as angry. The study revealed that neural correlates of multisensory processing was aberrant in SAD and it was related to the interpretation bias to multimodal social cues in multiple processing stages. Our findings suggested that deficit in multisensory processing might be an important factor in the psychopathology of SA.